International Year of Astronomy (IYA 2009): Selected Resources. - Mandy Taha; Joseph R. Kraus (Issues in Science and Technology Librarianship)
The article reviews web sites on general astronomy and 2009 International Year of Astronomy (IYA) such as the following, available at http://www.astronomy2009.org, 100 Hours of Astronomy available at http://www.100hoursofastronomy.org and Dark Skies Awareness available at http://www.darkskiesawareness.org.